LINGUA-CULTURE AS ONE OF THE MAIN AREAS OF LINGUISTIC RESEARCH (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses Lingua-culture which is one of the main areas of linguistic research. It explains the influences and differences that exist in different languages and cultures, as well as to study the interactions between different languages and cultures.